3, 2, 1, go! - McCully, Emily Arnold (New York : Holiday House, 2015)
Told she cannot step over the line to play school with the older girls, Min builds a catapult and flies over it, instead.
GRL: G.
Keywords: Play -- Juvenile fiction; Catapults (Aeronautics) -- Juvenile fiction; Play -- Fiction; Creative ability -- Fiction; Elephants -- Fiction